Identifying and Exploring the Candidate Susceptibility Genes of Cirrhosis Using the Multi-Tissue Transcriptome-Wide Association Study - Zhu, Xiao-Bo; Hou, Yu-Qing; Ye, Xiang-Yu; Zou, Yi-Xin; Xia, Xue-Shan; Yang, Sheng; Huang, Peng; Yu, Rong-Bin (Frontiers in Genetics, 2022)
Objective: We identify and explore the candidate susceptibility genes for cirrhosis and their underlying biological mechanism. Methods: We downloaded the genome-wide association studies summary data of 901 cirrhosis cases and 451,363 controls and integrated them with reference models of five potential tissues from the Genotype-Tissue Expression (GTEx) Project, including whole blood, liver, pancreas, spleen, and thyroid, to identify genes whose expression is predicted to be associated with cirrhosis. Then, we downloaded gene expression data of individuals with hepatocellular carcinoma from TCGA database to conduct differential expression analysis to validate these identified genes and explored their possible role in driving cirrhosis via functional enrichment and gene set enrichment analysis (GSEA). Results: We identified 10 significant genes (SKIV2L, JPH4, UQCC2, RP11-91I8.3, MAU2, ERAP1, PUS3, ZNF677, ARHGAP40, and SHANK3) associated with cirrhosis at a Bonferroni-corrected threshold of p < 0.01, among which two (SKIV2L and JPH4) were identified in the liver and five (SKIV2L, JPH4, MAU2, SHANK3, and UQCC2) were validated by differential expression analysis at an FDR-corrected threshold of p < 0.01. The enrichment analysis showed that the degradation process of RNA, which is enriched by 58 genes, is significantly under-enriched in liver cancer tissues (p = 0.0268). Conclusion: We have identified several candidate genes for cirrhosis in multiple tissues and performed differential genetic analysis using the liver cancer database to verify the significant genes. We found that the genes SKIV2L and JPH4 identified in the liver are of particular concern. Finally, through enrichment analysis, we speculate that the process of mRNA transcription and RNA degradation may play a role in cirrhosis.